Hepatocyte-Like Cells Derived from Mouse Induced Pluripotent Stem Cells Produce Functional Coagulation Factor IX in a Hemophilia B Mouse Model. Issue 7 (July 2016) - Wu, Yao-Ming; Huang, Yu-Jen; Chen, Poda; Hsu, Yu-Chen; Lin, Shu-Wha; Lai, Hong-Shiee; Lee, Hsuan-Shu
Hemophilia B (HB) is an inherited deficiency in coagulation factor IX (FIX) that leads to prolonged bleeding after injury. Although hepatocyte transplantation has been demonstrated to be an effective therapeutic strategy for HB, the quality and sources of hepatocytes still limit their application. Recently, stem cells were proposed as an alternative source of donor cells for cell-based therapy. Much research has been devoted to the properties of stem cells that can be differentiated into functional hepatocytes, thereby providing a new cell source for cell-based therapy. Induced pluripotent stem cells (iPSCs) represent a renewable source of hepatocytes for cell-based therapy; these cells exhibit pluripotency and differentiation ability and can be derived from somatic cells. These iPSCs are highly similar to embryonic stem cells (ESCs). We hypothesized that hepatocyte-like cells derived from iPSCs would have therapeutic efficiency in a mouse model of HB. To test this hypothesis, we differentiated iPSCs toward hepatocytes by stepwise protocol and then transplanted these cells into HB mice. We found that these cells shared many characteristics with hepatocytes, such as albumin synthesis, metabolic capacity, glycogen storage, and ureagenesis. Moreover, iPSC-derived hepatocyte transplantation led to increased coagulation factor IX activity, improved thrombus generation, and better hemostasis parameters, and the transferred cells were localized in the liver in recipient HB mice. In conclusion, our results clearly demonstrate that hepatocyte-like cells derived from iPSCs represent a potential cell source for cell-based therapy in the treatment of HB.